Discourse network on the revision of Indonesian information and electronic transaction law - Antonius O. Lapu Hamanduna; Putut Widjanarko (Jurnal Studi Komunikasi, 2023)
Freedom of speech is one of the pillars of democracy that is being problematised as new media technologies are increasingly used in people's lives. In Indonesia, this can be seen in the debate over the UU ITE, passed in 2008, one aspect of which regulates the dissemination of information, fake news, and the like in the digital public sphere. For its critics, several articles in the UU ITE threaten freedom of expression and are considered a factor in the democracy regression in Indonesia. Using the DNA method, this research investigates the discourse and actors involved in the debate and how the discourse network is shaped. There are two periods covered, namely October 2016 to December 2016 and February 2021 to June 2021, when the government issued an official explanation or further regulation of the ITE Law. From three prominent online media (Kompas.com, detik.com, and Tirto.id), 359 articles were obtained and then coded based on actors and discourses. Therefore, this research shows the discourse coalition on the issue of freedom of speech. This research shows that the second period of debate involved more actors and discourses and changed the discourse network. There are realignments of network coalition by the state apparatus to be more supportive towards the more democratic discourse, although it is not necessarily materialised in the policymaking decision.